A STUDY OF HYDROPONIC MELON CULTIVATIONS WITH SEVERAL SUBSTRATE MEDIA AND VARIETIES - Christy, Julieta; Putri, Lollie Agustina P.; Hanafiah, Diana Sofia (Journal of Community Research and Service, 2017)
AbstractMelon is a fruit plant that has a high nutritional value. A limited agricultural land encourages the application of alternatives planting method and utilizes local materials around the community as potential planting media towards resulting a high-yielding variety. One of the cultivation techniques is the use of the hydroponics system. The objective of this study is to determine the most suitable planting medium for melon varieties to be planted hydroponically. This research was conducted in the greenhouse at the sub-district of Medan Tuntungan in the city of Medan during May to August 2017. This research used Randomize Complete Block Design Factorial with 3 replications. The use of planting media consisted of charcoal husk, cocopeat, sawdust and sand; whereby the treatment of varieties consisted of Aramis F1, Amanta F1 and Red Aroma. The results showed that the best medium for hydroponics melon is charcoal husk highlighting significant result onto the plant height, number of leaves and fruit weight of crops, from the use of charcoal husk media.Keywords: hydroponic, soilless culture, melon, medium and variety